Poland’s Policy towards the Arctic:Key Areas and Priority Actions - Łuszczuk, Michał; Graczyk, Piotr; Stepien, Adam Maciej; Smieszek, Malgorzata (Polish Institute for International Affairs, 2015)
Given the multidimensional transformation taking place in the Arctic, it is timely to redefine and develop Poland’s engagement in the region. Although Poland has neither vital nor direct political and economic interests in the Arctic, the state’s multi-faceted involvement in international cooperation in that region may improve national security as well as enhance Poland’s international standing, especially in the EU, European and transatlantic dimensions. A clearly defined and comprehensive Arctic policy should be the foundation for further Polish engagement in the region. How this policy should look may be determined on the basis of the previous achievements, current potential, and identification of key rationales and of the areas for future activities.